Perlindungan Hukum terhadap Konsumen dalam Proses Transaksi Jual Beli secara Online di Marketplace - Dian Tirtha Rezkiyanti; Wahyudi, Wahyudi (Dialog Legal: Jurnal Syariah, Jurisprudensi dan Tata Negara, 2025)
The rapid advancement of technology in the world of information and transaction processes that occur in society which was initially done manually and has to visit existing traditional and modern stores, can now be done electronically or through social media. In article 1 paragraph 2 of the consumer protection law, the elements associated with consumers are related to people or who have the status as users of goods or services individually or legal entities. The purpose of holding this research is to find out the implementation of legal protection for consumers in the process of online buying and selling transactions through e-commerce. In the process of preparing the results of this scientific paper, the author uses a descriptive qualitative research method and in this research a method in the form of normative legal research is also used. This research was carried out through a literature study process with the use of supporting books, and journals to support the results of this research. The results of the study show that consumer protection needs to be carried out preventively and repressively in all aspects of the protection provided, so in this case the government has established a special institution, namely the Ombudsman and also the consumer protection agency to carry out the process of protection and supervision of consumers in Indonesia.